PELAYANAN PEMBAHARUAN E-KTP PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BANJARMASIN - Enly Hadiyanor (Jurnal Administrasi Publik dan Pembanguan, 2020)
In an effort to fulfill the obligation as a good Indonesian citizen of the city of Banjarmasin trying to obtain a personal identity in this case is a resident ID card (KTP), as a legitimate citizen in the Indonesian law. Therefore, if the identity card (KTP) is damaged/lost/change in identities or resident data, the community of Banjarmasin is trying to get the service from the population Office and civil registration of Banjarmasin City to the community. The goal that is to be achieved in this research is to find out what are the changes in the renewal service in the city of population and civil registration services of Banjarmasin and the renewal factors of resident identity card (KTP) and civil registration service of Banjarmasin City. This research is done with a qualitative approach with the type of research used is deskritif, the location of research in the Department of Population and Civil registration of Banjaramasin City. The technique of collecting data on this research is observation and interviews. The results of the renewal service of E-KTP of population and civil registration services Banjarmasin City can be concluded that in general, the renewal of E-KTP service in the population Office and civil registration of Banjarmasin City is not maximally well. The inhibitory factor in the renewal of E-KTP service in the population Office and civil registration of the city of Banjarmasin is from service. Suggestion submitted to the Ministry of Occupation and civil registration of the city of Banjarmasin based on the conclusion, researchers suggested to the population service and civil registration of Banjarmasin City to fix indicators that are considered still less successful so that the renewal service E-KTP in the population office and civil registration of the city of Banjarmasin can be categorized well.